How Consumer Engagement is Fuelling the Next Wave of Global E-Marketplace Growth - Danisa, Salma (International Journal of Research and Applied Technology (INJURATECH), 2024)
The transformation of the global electronic commerce landscape is currently shifting from a purely transactional model toward an ecosystem centered on consumer engagement. This research aims to analyze how digital engagement mechanisms—such as social features, gamification, and AI-driven personalization—have become the primary drivers of e-marketplace growth in the global market. Through a systematic literature review, this study finds that two-way interactions between platforms and users not only enhance retention but also significantly reduce customer acquisition costs. The findings indicate that "engagement" is no longer merely a supplementary element but a core growth engine defining the new wave of e-commerce. This article offers a theoretical contribution in the form of an Engagement-Driven Growth framework and provides practical recommendations for platform managers to prioritize experiential value over mere transaction volume.